Focus on Oral Interaction: Research-led guide exploring the role of oral interaction for second language learning - Oliver, Rhonda; Philp, J. (Oxford University Press, 2014)
Focus on Oral Interaction explores the role of oral interaction for second language learning from cognitive, social, pedagogical, and linguistic perspectives, with a focus on research relevant to English language learners aged 6-16. It emphasizes the important role played by oral language in classrooms. Featuring real classroom data and summaries of research studies, Focus on Oral Interaction shows you how theory relates to practice. Activities help you relate research and theory on oral interaction to your own teaching context.